Age Associated Microbiome and Microbial Metabolites Modulation and Its Association With Systemic Inflammation in a Rhesus Macaque Model - Pallikkuth, Suresh; Mendez, Roberto; Russell, Kyle; Sirupangi, Tirupataiah; Kvistad, Daniel; Pahwa, Rajendra; Villinger, Francois; Banerjee, Santanu; Pahwa, Savita (Frontiers in Immunology, 2021)
Aging is associated with declining immunity and inflammation as well as alterations in the gut microbiome with a decrease of beneficial microbes and increase in pathogenic ones. The aim of this study was to investigate aging associated gut microbiome in relation to immunologic and metabolic profile in a non-human primate (NHP) model. 12 geriatric (age 19-24 years) and 4 young adult (age 3-4 years) Rhesus macaques were included in this study. Immune cell subsets were characterized in PBMC by flow cytometry and plasma cytokines levels were determined by bead based multiplex cytokine analysis. Stool samples were collected by ileal loop and investigated for microbiome analysis by shotgun metagenomics. Serum, gut microbial lysate, and microbe-free fecal extract were subjected to metabolomic analysis by mass-spectrometry. Our results showed that the gut microbiome in geriatric animals had higher abundance of Archaeal and Proteobacterial species and lower Firmicutes than the young adults. Highly abundant microbes in the geriatric animals showed a direct association with plasma biomarkers of inflammation and immune activation such as neopterin, CRP, TNF, IL-2, IL-6, IL-8 and IFN-γ. Significant enrichment of metabolites that contribute to inflammatory and cytotoxic pathways was observed in serum and feces of geriatric animals compared to the young adults. We conclude that aging NHP undergo immunosenescence and age associated alterations in the gut microbiome that has a distinct metabolic profile. Aging NHP can serve as a model for investigating the relationship of the gut microbiome to particular age-associated comorbidities and for strategies aimed at modulating the microbiome.